Design of Web-Based Taxpayer Data Collection Information System - Harisanul Arifin (Ali Institute of Reseach and Publication, 2024)
The aim of this research is to design a taxpayer data collection administration website to make it more accurate, work efficiency and effectiveness better and increase work efficiency and effectiveness. To solve the problem of less than optimal tax payer data collection. In this research, the waterfall method was used. And this system is designed to help officers collect taxpayer data better and more easily via the website. It is hoped that the results of the research will make it easier for officers to carry out their duties and increase efficiency in serving taxpayers at KPP Pratama Medan Petisah. And it can be concluded that the web-based taxpayer data information system designed using the waterfall method has succeeded in overcoming the challenges of efficiency and effectiveness of tax data collection.